Acid/Base Multi‐Ion Exchange Membrane‐Based Electrolysis System for Water Splitting. Issue 8 (18th January 2017) - Nazemi, Mohammadreza; Padgett, James; Hatzell, Marta C.
Abstract: Water electrolysis potentially represents an environmentally friendly method for scalable hydrogen production and for intermittent renewable energy storage. Yet cost and high reaction overpotentials limit widespread implementation. Here, an electrolysis cell architecture that uses dissimilar electrolytes is shown to minimize the kinetic and thermodynamic considerations ascribed to electrolysis. The use of multiple monopolar ion exchange membranes (anion and cation selective) and multiple chambers (anolyte, catholyte, middle) allows stable electrolysis operation while a pH gradient is maintained across the electrolysis cell. This reduced the hydrogen and oxygen evolution onset potential by 0.65 ± 0.03 and 0.62 ± 0.01 V, resulting in a whole cell onset potential for water splitting of 0.79 ± 0.02 V. The reduced onset potential was demonstrated for >15 h of operation under fixed current density, resulting in a decrease in energy consumption by 56 % when compared to similar pH electrolysis cells. Abstract : Triple cell and two membranes : A membrane‐based electrolysis cell consisting of multiple monopolar ion‐exchange membranes (anion and cation selective) and multiple chambers (anolyte, middle, catholyte) is assembled. This configuration allows stable electrolysis operation while a pH gradient is maintained across the cell. This setup results in a reduction in the thermodynamic potential needed for water splitting.